Discrete dynamical systems with invariant asymptotically stable toroidal manifold - Samoilenko, A. M.; Slyusarchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain conditions for asymptotic stability of quasiperiodic trajectories of discrete dynamical systems in the case of infinite-dimensional Banach space.